2016
DOI: 10.1016/j.ecoser.2016.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Shedding light on the usability of ecosystem services–based decision support systems: An eye-tracking study linked to the cognitive probing approach

Abstract: a b s t r a c tThe requirements for communicating ecosystem services (ES) information often are not considered in operationalizing ES concepts. In particular, the heterogeneous uses of ES require different functionalities and qualities for the information provided, which must be considered when processing ES data into different types of information. The relevant factors that influence the usability of ES information include the users' knowledge and cognitive ability as well as case study-specific factors. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Variety of studies reported the use of eye tracking in design, for example in graphic design and other computer-based visual evaluation methods, which are used to measure the distribution of visual attention (Poole and Ball, 2005;Hollander et al, 2019). In a study from 2016, eye-tracking was used to assess computer-based visual tools, which help decision-making to investigate ecosystem services (Klein et al, 2016). It has been suggested that the ability of users to understand ecosystem services can be improved through the use of such decision support systems.…”
Section: Eye Tracking In Designmentioning
confidence: 99%
“…Variety of studies reported the use of eye tracking in design, for example in graphic design and other computer-based visual evaluation methods, which are used to measure the distribution of visual attention (Poole and Ball, 2005;Hollander et al, 2019). In a study from 2016, eye-tracking was used to assess computer-based visual tools, which help decision-making to investigate ecosystem services (Klein et al, 2016). It has been suggested that the ability of users to understand ecosystem services can be improved through the use of such decision support systems.…”
Section: Eye Tracking In Designmentioning
confidence: 99%
“…In our CSs, as in many others (Lewan and Söderqvist 2002, Baker et al 2013, MacDonald et al 2014, Mascarenhas et al 2016, various levels of understanding of the concept and of ecosystem https://www.ecologyandsociety.org/vol23/iss2/art27/ functioning were reported. In fact, the understanding of the concept depends on how it is introduced (Klein et al 2016). It is well known that methods can influence outcomes of participatory exercises (Kenter et al 2011, Malinga et al 2013, Raymond et al 2014.…”
Section: Opportunities and Challenges For The Ecosystem Service Conceptmentioning
confidence: 99%
“…In contrast, the valley bottoms are mostly affected by the intensification of agricultural use as well as the expansion of settlements and infrastructure [ 14 , 15 ], increasing the share of less preferred artificial features and landscape types [ 16 18 ], which also induces a decline in aesthetic landscape values [ 11 , 14 ]. As such developments are ongoing due to legacy effects [ 19 , 20 ] and expected future demand for ecosystem services [ 14 ], profound knowledge about landscape preferences is of high importance to support decision-making in developing effective strategies for maintaining preferred visual landscape characteristics and fostering positive benefits for human well-being [ 11 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies focused on the beauty of natural environments, e.g., forests [ 38 , 45 47 ], underwater reefs [ 48 ] or lakescapes [ 49 ] as well as visual preferences in urban environments and urban green spaces, e.g., [ 33 , 50 55 ]. Eye-tracking experiments can also support the understanding individual’s perceptions and cognitive processes for decision-making related to landscape and ecosystem service planning as shown for mountain landscapes [ 21 ] and forest landscapes [ 47 ]. In summary, eye-tracking is a well-situated approach in context with landscape perception without the language filter [ 55 ].…”
Section: Introductionmentioning
confidence: 99%